2016
DOI: 10.1016/j.foodres.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of cocoa beans and chocolate assessed by FTIR

Abstract: The total antioxidant capacity (TAC) and total phenolic compounds (TPC) of cocoa beans and chocolate produced from spontaneous and inoculated fermentations of different cocoa varieties were evaluated. Fourier transform infrared spectroscopy (FTIR), as well as conventional methods: 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), was used to determine TAC and TPC. Chocolate showed higher (p<0.05) TPC (47.17-57.16mgGAE/g) and TAC (1.66-2.33mMTE/g and 8.86-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 40 publications
9
61
1
2
Order By: Relevance
“…The wavelengths related by the regions 3562-3322 cm −1 can be referring to the phenyl group (attributed to the stretch of O\H), 2925-2854 cm −1 (attributed to the stretch of the C\H of aromatic ring), 1244-1064 cm −1 (attributed to C\H stretch), and 992-680 cm −1 (attributed to angular deformation of C\H of aromatic ring). [23] (Figure 2) presents similar peaks reported in cocoa from the other cultivars and presents similarity with the FTIR spectra of roasted coffee. Craig et al [16] reported peaks in wavelengths 2922, 2852, 1743, and 1153 cm −1 ; the first three bands are associated with lipid absorption, and the last peak has been associated with polysaccharides; the region 1130-950 cm −1 is associated with strong carbohydrate absorbtion, and arabinogalactans may absorb at 1065 cm −1 and 1020 cm −1 .…”
Section: Mathematical Expressionsupporting
confidence: 69%
“…The wavelengths related by the regions 3562-3322 cm −1 can be referring to the phenyl group (attributed to the stretch of O\H), 2925-2854 cm −1 (attributed to the stretch of the C\H of aromatic ring), 1244-1064 cm −1 (attributed to C\H stretch), and 992-680 cm −1 (attributed to angular deformation of C\H of aromatic ring). [23] (Figure 2) presents similar peaks reported in cocoa from the other cultivars and presents similarity with the FTIR spectra of roasted coffee. Craig et al [16] reported peaks in wavelengths 2922, 2852, 1743, and 1153 cm −1 ; the first three bands are associated with lipid absorption, and the last peak has been associated with polysaccharides; the region 1130-950 cm −1 is associated with strong carbohydrate absorbtion, and arabinogalactans may absorb at 1065 cm −1 and 1020 cm −1 .…”
Section: Mathematical Expressionsupporting
confidence: 69%
“…The hydroxyl functionality is an integral part of most phenolic phytochemicals, such as polyphenols and flavonoids, to provide a relative ranking of extracts in terms of antioxidant activity. The bands at 2924-2854 cm −1 (attributed to the stretch of the C-H of aromatic ring) assigned to the aromatic ring (Batista et al, 2016) were found in all extracts. The sharp absorption peak at frequency 1739 cm -1 was assigned to -C=O stretching vibration in carbonyl compounds, which may be characterized by the presence of high polyphenol content in the samples (Kiat et al, 2014).…”
Section: Evaluation By Ft-irmentioning
confidence: 89%
“…1. FT-IR spectra of solvent extracts CMW, CEW, CME and CEE of black cumin seeds: MW-0 -pretreated at 0 min, MW-1 -pretreated at 1 min, MW-2 -pretreated at 2 min, MW-3 -pretreated at 3 min; CME -methanol extract, CMW -70% methanol in water extract, CEE -ethanol extract, CEW -70% ethanol in water extract www.food.actapol.net/ about the structure of polyphenols were found in the regions 3390-3352 cm −1 (attributed to the stretch of O-H) and 1049 cm −1 (attributed to C-H stretch) (Batista et al, 2016) and recognized in all the solvent extracts. The hydroxyl functionality is an integral part of most phenolic phytochemicals, such as polyphenols and flavonoids, to provide a relative ranking of extracts in terms of antioxidant activity.…”
Section: Evaluation By Ft-irmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocoa seeds are subdivided into cotyledon and embryo, protected by a pulp and a seed coat. They are basically constituted of 54% fat, 1.5% theobromine and caffeine, and polyphenol content represents 12 to 20% of the dry weight of the whole seed [ 116 ]. Polyphenol compounds are stored in the pigment cells of the cotyledons and are responsible for imparting bitterness and astringency to the cocoa fruit [ 117 ].…”
Section: Vegetables Popularly Consumed In Brazil As Polyphenol Soumentioning
confidence: 99%